7-series aluminum material corrosion inhibition composition and application thereof in surface corrosion prevention of 7-series aluminum material
Through the phosphorus-free corrosion inhibiting composition, alkali metal silicates, polyhydroxy acids and fatty acids are used to form an efficient corrosion-resistant film, which solves the environmental, health and performance problems of the corrosion-proof method of aluminum materials in the prior art in the existing technology , achieving environmentally friendly, stable and efficient corrosion protection.
Patent Information
- Application Number
- CN202411265913.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-10
AI Technical Summary
The existing anti-corrosion methods for 7-series aluminum have problems such as environmental and health hazards caused by the use of organic solvents, high costs, affecting the appearance and processing of metal surfaces, and the corrosion inhibitor performance is single and the storage stability is not high.
Using phosphorus-free corrosion inhibiting compositions, including alkali metal silicates, polyhydroxy acid alkali metal salts and fatty acid alkali metal salts, to form efficient anti-antibody by optimizing component ratios and the use of film-forming agents and surfactants. Corrode the film to avoid the use of oxidative corrosion inhibitors and phosphorus.
The corrosion resistance effect of 7 Series aluminum with environmental protection and high storage stability is achieved, the corrosion rate is reduced, the corrosion resistance of aluminum is improved, and the insufficient usage and environmental impact are avoided.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to a 7-series aluminum material corrosion inhibition composition and application of the composition in surface corrosion protection of 7-series aluminum materials. Background Art
[0002] 7 series aluminum has high hardness but poor corrosion resistance. During production, transportation and storage, 7 series aluminum tends to corrode. One way to reduce the tendency of corrosion is to use corrosion inhibitors, but there are still many problems with the existing anti-corrosion methods for aluminum alloy materials. First, the use of anti-corrosion coatings has low bonding strength for aluminum alloy materials and is prone to falling off: a large amount of organic solvents are used in existing coatings, which are costly and harmful to the environment and human health. In addition, the use of coatings for anti-corrosion will change the appearance of the metal surface and affect subsequent processing. Generally, fine processing will not use coatings for anti-corrosion. Second, anodizing technology. Anodizing is generally carried out in the later stage of metal processing, and is accompanied by processes such as metal color finding, which affects the appearance of the metal. This technology has requirements for equipment and environment. Third, corrosion inhibitor treatment is simple to operate, has low requirements for environmental equipment, and can be applied by soaking. The existing corrosion inhibitor formula has relatively simple performance and a single film-forming mechanism on the metal surface, making it difficult to form a complete and dense anti-corrosion film.
[0003] Patent CN 115852376 A discloses a corrosion inhibitor for 7 series aluminum materials. Since it uses an oxidizing corrosion inhibitor component, if the dosage is insufficient, pitting corrosion will cause property losses. In addition, a large amount of corrosion inhibitor components such as phosphorus and oxidants are used, which is not conducive to environmental protection and has low storage stability. Summary of the invention
[0004] One of the purposes of the present invention is to provide a new 7-series aluminum corrosion inhibition composition, which does not use phosphorus-containing components or oxidative corrosion inhibitor components and has the characteristics of environmental protection and high storage stability.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] The 7 series aluminum corrosion inhibition composition comprises the following components in parts by weight:
[0007] Alkali metal silicate, 1 part;
[0008] Polyhydroxy acid alkali metal salt, 1-5 parts;
[0009] Alkali metal salt of fatty acid, 0.1 to 1.5 parts.
[0010] The present invention does not use an oxidizing corrosion inhibitor, can avoid the defect of pitting corrosion caused by insufficient dosage, does not use a phosphorus-containing corrosion inhibitor component, and has the advantage of being environmentally friendly.
[0011] By way of non-limiting example, the number of parts of the alkali metal salt of the polyhydroxy acid is 1.5, 2, 2.5, 3, 3.5, 4, 4.5, etc.
[0012] By way of non-limiting example, the fraction of alkali metal salt of fatty acid is 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, etc.
[0013] In the above technical solution, the composition of the alkali metal silicate preferably conforms to the following formula 1:
[0014] M2O﹒ nSiO2, formula 1;
[0015] Wherein M represents an alkali metal, n is the molar ratio of SiO2 to M2O, also known as the modulus, and more preferably n is 0.5 to 3, for example but not limited to n is 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8 and the like.
[0016] Those skilled in the art will know that when n is 0.5, the substance described in Formula 1 corresponds to an alkali metal orthosilicate, such as sodium orthosilicate; when n is 1, the substance corresponding to Formula 1 is an alkali metal metasilicate, such as sodium metasilicate, and the commercially available varieties of sodium metasilicate include anhydrous sodium metasilicate, pentahydrate sodium metasilicate and nonahydrate sodium metasilicate. The commonly used sodium silicate in industry, also called water glass, also conforms to Formula 1, but n is usually controlled to be 1 to 3. These specific forms of alkali metal silicates can all be used in the present invention, and can all achieve comparable technical effects.
[0017] In the above technical solution, the polyhydroxy acid-alkali metal salt preferably conforms to the following formula 2:
[0018]
[0019] Wherein Q represents an alkali metal, and m=3 to 5;
[0020] For example, when m=3, it is an alkali metal salt of 2,3,4,5-tetrahydroxypentanoic acid, when m=4, it is an alkali metal salt of 2,3,4,5,6-pentahydroxyhexanoic acid (gluconic acid is this substance), when m=5, it is an alkali metal salt of 2,3,4,5,6,7-hexahydroxyheptanoic acid (commonly known as glucoheptonic acid or glucoheptonic acid is this substance).
[0021] In the above technical solution, the fatty acid alkali metal salt preferably conforms to RCOOT, wherein R is a C5-C8 straight-chain or branched aliphatic hydrocarbon group, and T represents an alkali metal. As non-limiting examples, examples of fatty acid alkali metal salts are sodium hexanoate, sodium heptanoate, sodium octanoate, sodium isooctanoate (also known as sodium 2-ethylhexanoate), sodium 2-octenoate, sodium nonanoate, and the like. We believe that the fatty acid radical in the fatty acid alkali metal salt can form an adsorption layer on the surface of the aluminum material, reducing the corrosion tendency of the aluminum material.
[0022] More particularly, we have found that when the fatty acid alkali metal salt includes a first fatty acid alkali metal salt and a second fatty acid alkali metal salt, the first fatty acid alkali metal salt is a straight-chain saturated fatty acid alkali metal salt, and the second fatty acid alkali metal salt is an unsaturated fatty acid alkali metal salt or a branched fatty acid alkali metal salt, the first fatty acid alkali metal salt and the second fatty acid alkali metal salt have a mutual promotion effect in improving the corrosion resistance of 7 series aluminum materials. Preferably, the weight ratio of the second fatty acid alkali metal salt to the first fatty acid alkali metal salt is greater than 0 and less than 0.2, for example but not limited to 0.01, 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, etc.
[0023] In the above technical solution, the alkali metal in the alkali metal silicate, the alkali metal in the polyhydroxy acid alkali metal salt and the alkali metal in the fatty acid alkali metal salt are independently preferably potassium or sodium.
[0024] In the above technical solution, the corrosion inhibition composition preferably includes 0.1 to 1.5 parts of the film-forming agent, for example but not limited to 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.3 parts, 1.4 parts, etc.
[0025] In the above technical solution, the film-forming agent preferably conforms to the following formula 3:
[0026]
[0027] in:
[0028] R1 and R2 are independently C1-C3 alkyl, such as methyl, ethyl, n-propyl or isopropyl;
[0029] X is an aliphatic group having 3 to 10 carbon atoms (for example, but not limited to, 4, 5, 6, 7, 8, 9, etc.), the aliphatic group contains an amino group, and the amino group includes a primary amino group and a secondary amino group; preferably, the ratio of the number of atoms of the amino group N in X to the number of atoms of Si in Formula 3 is 2 or more (for example, but not limited to, 2, 3, 4, 5, 6, etc.), and X is connected to Si in Formula 3 through a carbon atom in X;
[0030] Y is an aliphatic group having 3 to 10 carbon atoms, the aliphatic group contains an amino group, and the amino group includes a primary amino group and a secondary amino group; preferably, the ratio of the number of atoms of the amino group N in Y to the number of atoms of Si in Formula 3 is 2 or more (for example but not limited to 2, 3, 4, 5, 6, etc.), and Y is connected to Si in Formula 3 through the carbon atom in Y; or Y is a C1 to C3 alkoxy group (such as methoxy, ethoxy, n-propoxy or isopropoxy).
[0031] As a non-limiting example, the film-forming agent described in Formula 3 can be:
[0032] N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (CAS No. 3069-29-2), N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane (CAS No. 1760-24-3), N-β-(aminoethyl)-γ-aminopropyltriethoxysilane (CAS No. 5089-72-5), γ-diethylenetriaminopropyltrimethoxysilane (CAS No. 35141-30-1), etc. For comparison only, the components shown in Formula 3 in the Examples and Comparative Examples all use γ-diethylenetriaminopropyltrimethoxysilane.
[0033] In the above technical scheme, the corrosion inhibition composition preferably includes 0.1 to 5 parts (for example, but not limited to 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, etc.) of a surfactant as a dispersant, and the surfactant is preferably an anionic surfactant or a nonionic surfactant.
[0034] Preferably, the anionic surfactant includes at least one selected from the group consisting of alkyl sulfates, alkylbenzene sulfonates and alcohol ether sulfates, and the anionic surfactant is preferably an alkali metal salt or a triethanolammonium salt; for example but not limited to, the alkyl sulfate is sodium dodecyl sulfate, referred to as K12; for example but not limited to, the alkylbenzene sulfonate can be sodium dodecylbenzene sulfonate, referred to as LAS; for example but not limited to, the alcohol ether sulfate is fatty alcohol polyoxyethylene ether sulfate, the fatty alcohol is a C12-C15 fatty alcohol, and the number of ethylene oxide units is 2-3.
[0035] The nonionic surfactant is further preferably a nonionic surfactant with an HLB value of 8 to 18 (for example, but not limited to, HLB values of 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5, 16, 16.5, 17, 17.5), and most preferably a nonionic surfactant with an HLB value of 13 to 18.
[0036] Preferably, the nonionic surfactant includes at least one selected from the group consisting of ethylene oxide propylene oxide copolyether, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and fatty amine polyoxyethylene ether.
[0037] The surfactants can all achieve comparable dispersing effects. For example and comparison only, sodium dodecylbenzene sulfonate is used in the embodiments of the present invention.
[0038] In the above technical solution, the corrosion inhibition composition may be in a solid phase form.
[0039] In the above technical scheme, the corrosion-inhibiting composition can be made into a liquid form, that is, the corrosion-inhibiting composition includes a solvent, the solvent is water or mainly water, and the amount of water used can be to make the corrosion inhibitor combination into a high-concentration liquid form, which can be diluted to the concentration required for the corrosion-inhibiting construction site when used, or the amount of water used can be to directly prepare the corrosion-inhibiting composition into the concentration required for the corrosion-inhibiting construction site. The liquid form of the composition can be selected from 30 to 1000 parts of water (for example, but not limited to 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 100 parts, 150 parts, 200 parts, 250 parts, 300 parts, 350 parts, 400 parts, 500 parts, 600 parts, 700 parts, 800 parts, 900 parts, etc.).
[0040] Those skilled in the art know that defoamers can be used, and defoamers can be added in advance to the combination group or added at the corrosion inhibition construction operation site. Especially when the composition of the present invention contains a surfactant, foam is easily generated at a larger corrosion inhibition construction operation site. Although the foam itself has no obvious effect on the corrosion inhibition performance of the composition of the present invention, the foam will have an adverse effect on the construction environment. From this aspect, the composition of the present invention can also include a defoamer. As for the type and amount, those skilled in the art can make reasonable choices according to the situation, and do not have to pay creative labor. Only non-limiting examples are made, such as the amount of defoamer is 0.01 to 2 parts, and more specific non-limiting examples are such as but not limited to 0.05 parts, 0.1 parts, 0.5 parts, 1 parts, 1.5 parts, etc. Only for the same period of time, in the case of using a defoamer in the specific embodiment of the present invention, the amount of the defoamer is 0.1 parts, and the defoamer is a water-soluble polyether defoamer supplied by Wuhan Xunshi Company, and the trade name is WESTARXF-EP 101.
[0041] There is no particular limitation on the preparation method of the corrosion inhibition composition of the present invention. A person skilled in the art can obtain the corrosion inhibition composition of the present invention by uniformly mixing the components required by the composition.
[0042] In the present invention, the amounts of alkali metal silicates, polyhydroxy acid alkali metal salts and fatty acid alkali metal salts are all measured in the form of anhydrous substances; the amounts of film formers, surfactants and defoamers used in the present invention are all measured in terms of their respective effective substances.
[0043] The second object of the present invention is to provide the application of the above-mentioned corrosion inhibition composition in the surface corrosion protection of 7 series aluminum materials.
[0044] The technical key of the present invention is the selection of components in the corrosion inhibition composition. For the construction process conditions in the corrosion inhibition of the surface of 7 series aluminum materials, those skilled in the art can adopt those known in the prior art to achieve comparable corrosion inhibition effects without having to engage in creative work.
[0045] Evaluation method of the corrosion inhibitor composition of the present invention:
[0046] 1. Overview of evaluation methods
[0047] The method is to compare 7050 aluminum test pieces treated with corrosion inhibitor and those not treated with corrosion inhibitor (the 7050 aluminum test piece treated with corrosion inhibitor is used as the test test piece, and the 7050 aluminum test piece not treated with corrosion inhibitor is used as the blank test piece) after being fully immersed in a destructive corrosion solution at a certain temperature for a specified time, observe the appearance, measure the weight change of the aluminum test piece to calculate the corrosion rate, and calculate the corrosion inhibition rate through the corrosion rate. The larger the corrosion inhibition rate, the better the corrosion inhibition effect of the corrosion inhibitor.
[0048] 2. Main instruments and materials
[0049] Analytical balance: maximum weighing 100g, actual graduation value 0.1mg;
[0050] Constant temperature water bath;
[0051] Ultrasonic cleaning machine;
[0052] Enamel tank: 600mL;
[0053] Test piece: 7050 aluminum, dimensions see Figure 1 .
[0054] 3. Experimental Preparation
[0055] 3.1 Destructive Corrosive Solutions
[0056] The destructive corrosion solution is a 35±1g / L sodium chloride aqueous solution.
[0057] 3.2 Test piece processing
[0058] 3.2.1 Grinding and cleaning
[0059] Grind the 7050 aluminum test pieces in Section "2" with No. 1000 sandpaper to remove aluminum rust, clean them with acetone, dry them with hot air, put them in a desiccator filled with color-changing silica gel to cool overnight, and set them aside.
[0060] 3.2.2 Test specimens
[0061] Put 600ml of the corrosion inhibitor composition evaluation solution into a 600ml enamel jar, place it in a (25±2)℃ constant temperature water bath to heat it. After reaching the temperature, put in three test pieces obtained in Section "3.2.1", hang and immerse them in the test solution (there is no contact between the test pieces and the enamel jar around the test pieces) and let them stand for 20 minutes; take them out and put them in a pure water ultrasonic cleaning tank, wash them at 25℃ for 2 minutes (change the pure water after each wash), and wash them three times. Then wash them twice with anhydrous ethanol, blow dry with hot air, put them in a desiccator filled with color-changing silica gel to cool overnight, and set them aside.
[0062] 4. Experimental steps
[0063] 4.1. Test steps of the specimen after corrosion inhibition treatment
[0064] Weigh the test specimens obtained in Section "3.2.2" with a balance (accurate to 0.1 mg). Take 600 ml of the destructive corrosion solution in Section "3.1" and put it into a 600 mL enamel cylinder, place it in a (40±2)℃ constant temperature water bath to heat it. After reaching the temperature, put in three test specimens weighed above, and each test specimen is suspended and fully immersed in the destructive corrosion solution (there is no contact between the test specimens and between the test specimens and the enamel cylinder); after being placed statically at a constant temperature for 6 hours, take out the test specimens, immediately rinse them with clean water, then wash them twice with anhydrous ethanol, blow dry them with hot air, observe the appearance, put them in a desiccator filled with color-changing silica gel to cool overnight, and weigh them (accurate to 0.1 mg).
[0065] 4.1.1. Appearance rating
[0066] The surface of the test piece after the corrosion test shall be graded according to the following standards.
[0067] Level 0: No noticeable changes on the surface;
[0068] Level 1: Slight uniform discoloration or loss of gloss on the surface;
[0069] Level 2: uneven surface discoloration, loss of gloss, and local spots;
[0070] Level 3: Severe surface discoloration or corrosion.
[0071] 4.1.2. Corrosion rate calculation
[0072] The corrosion rate of each test piece was calculated according to the following formula:
[0073] γ=87600×(m0-m) / Atρ
[0074] γ---Corrosion rate of each test piece, unit: mm / a;
[0075] m0---mass of the test piece before the test, g;
[0076] m---mass of the test piece after the test, g;
[0077] A----surface area of test piece, g / cm 2 ;
[0078] ρ---Density of the test piece, g / cm 3 ;
[0079] t---test time, h.
[0080] The arithmetic mean of the corrosion rates of the three test pieces is taken as the corrosion rate γ under the test conditions. 腐蚀 .
[0081] 4.2 Blank test steps
[0082] The same as Section 5.1 except that the test piece obtained in Section 3.2.1 is used instead of the test piece obtained in Section 3.2.2.
[0083] The arithmetic mean of the corrosion rates of the three test pieces is taken as the corrosion rate γ0 of the blank experiment.
[0084] 4.3 Calculation of corrosion inhibition rate
[0085] Substitute the corrosion rates obtained in Sections "4.1" and "4.2" into the following formula to calculate the slow release rate:
[0086] Corrosion inhibition rate = ((γ0-γ 腐蚀 ) / γ0)×100% BRIEF DESCRIPTION OF THE DRAWINGS
[0087] Figure 1 This is a schematic diagram of the 7050 aluminum test piece dimensions. DETAILED DESCRIPTION
[0088] The present invention is described in detail below by specific implementation modes and examples:
[0089] [Example 1]
[0090] 1. Preparation of Corrosion Inhibitor Concentrate
[0091] Add 1 part by weight of sodium metasilicate and 2 parts by weight of sodium gluconate to 30 parts by weight of deionized water, stir to dissolve, then add deionized water until the total weight of all materials is 50 parts by weight, stir evenly, and obtain a concentrated solution of the corrosion inhibitor composition.
[0092] 2. Preparation of solution for corrosion inhibitor composition evaluation
[0093] The concentrated solution of the corrosion inhibitor composition was diluted with deionized water to obtain a dilute solution of the corrosion inhibitor composition with a sodium metasilicate concentration of 0.1%, which was used as a solution for evaluating the corrosion inhibition performance of the corrosion inhibitor composition.
[0094] After evaluation, the appearance rating of the test piece was 3, and the corrosion inhibition rate was 21.7%.
[0095] [Example 2]
[0096] 1. Preparation of Corrosion Inhibitor Composition Concentrate
[0097] Add 1 part by weight of sodium metasilicate, 2 parts by weight of sodium gluconate, 1 part by weight of sodium octanoate and 0.1 part by weight of defoamer to 30 parts by weight of deionized water, stir to dissolve, then add deionized water to make the total weight of all materials 50 parts by weight, stir evenly, and obtain a concentrated solution of the corrosion inhibitor composition.
[0098] 2. Preparation of solution for corrosion inhibitor composition evaluation
[0099] The concentrated solution of the corrosion inhibitor composition was diluted with deionized water to obtain a dilute solution of the corrosion inhibitor composition with a sodium metasilicate concentration of 0.1%, which was used as a solution for evaluating the corrosion inhibition performance of the corrosion inhibitor composition.
[0100] After evaluation, the appearance rating of the test piece was 2, and the corrosion inhibition rate was 61.3%.
[0101] [Example 3]
[0102] 1. Preparation of Corrosion Inhibitor Composition Concentrate
[0103] Add 1 part by weight of sodium metasilicate, 2 parts by weight of sodium gluconate, 1 part by weight of sodium octanoate, 1 part by weight of γ-diethylenetriaminopropyltrimethoxysilane and 0.1 part by weight of defoamer to 30 parts by weight of deionized water, stir to dissolve, then add deionized water to a total weight of 50 parts by weight of all materials, stir evenly, and obtain a concentrated solution of the corrosion inhibitor composition.
[0104] 2. Preparation of solution for corrosion inhibitor composition evaluation
[0105] The concentrated solution of the corrosion inhibitor composition was diluted with deionized water to obtain a dilute solution of the corrosion inhibitor composition with a sodium metasilicate concentration of 0.1%, which was used as a solution for evaluating the corrosion inhibition performance of the corrosion inhibitor composition.
[0106] After evaluation, the appearance rating of the test piece was 1, and the corrosion inhibition rate was 84.5%.
[0107] [Example 4]
[0108] 1. Preparation of Corrosion Inhibitor Composition Concentrate
[0109] To 30 parts by weight of deionized water, add 1 part by weight of sodium metasilicate, 2 parts by weight of sodium gluconate, 1 part by weight of sodium octanoate, 1 part by weight of γ-diethylenetriaminopropyltrimethoxysilane, 1.5 parts by weight of LAS and 0.1 part by weight of defoamer, stir to dissolve, then add deionized water to a total weight of 50 parts by weight of all materials, stir evenly, and obtain a concentrated solution of the corrosion inhibitor composition.
[0110] 2. Preparation of solution for corrosion inhibitor composition evaluation
[0111] The concentrated solution of the corrosion inhibitor composition was diluted with deionized water to obtain a dilute solution of the corrosion inhibitor composition with a sodium metasilicate concentration of 0.1%, which was used as a solution for evaluating the corrosion inhibition performance of the corrosion inhibitor composition.
[0112] After evaluation, the appearance rating of the test piece was 1, and the corrosion inhibition rate was 90.3%.
[0113] [Example 5]
[0114] 1. Preparation of Corrosion Inhibitor Composition Concentrate
[0115] To 30 parts by weight of deionized water, add 1 part by weight of sodium metasilicate, 2 parts by weight of sodium gluconate, 1 part by weight of sodium isooctanoate, 1 part by weight of γ-diethylenetriaminopropyltrimethoxysilane, 1.5 parts by weight of LAS and 0.1 part by weight of defoamer, stir to dissolve, then add deionized water to a total weight of 50 parts by weight of all materials, stir evenly, and obtain a concentrated solution of the corrosion inhibitor composition.
[0116] 2. Preparation of solution for corrosion inhibitor composition evaluation
[0117] The concentrated solution of the corrosion inhibitor composition was diluted with deionized water to obtain a dilute solution of the corrosion inhibitor composition with a sodium metasilicate concentration of 0.1%, which was used as a solution for evaluating the corrosion inhibition performance of the corrosion inhibitor composition.
[0118] After evaluation, the appearance rating of the test piece was 1, and the corrosion inhibition rate was 82.6%.
[0119] [Example 6]
[0120] 1. Preparation of Corrosion Inhibitor Composition Concentrate
[0121] To 30 parts by weight of deionized water, add 1 part by weight of sodium metasilicate, 2 parts by weight of sodium gluconate, 1 part by weight of sodium 2-octenoate, 1 part by weight of γ-diethylenetriaminopropyltrimethoxysilane, 1.5 parts by weight of LAS and 0.1 part by weight of defoamer, stir to dissolve, then add deionized water to a total weight of 100 parts by weight of all materials, stir evenly, and obtain a concentrated solution of the corrosion inhibitor composition.
[0122] 2. Preparation of solution for corrosion inhibitor composition evaluation
[0123] The concentrated solution of the corrosion inhibitor composition was diluted with deionized water to obtain a dilute solution of the corrosion inhibitor composition with a sodium metasilicate concentration of 0.1%, which was used as a solution for evaluating the corrosion inhibition performance of the corrosion inhibitor composition.
[0124] After evaluation, the appearance rating of the test piece was 1, and the corrosion inhibition rate was 88.7%.
[0125] [Example 7]
[0126] 1. Preparation of Corrosion Inhibitor Concentrate
[0127] To 30 parts by weight of deionized water, add 1 part by weight of sodium metasilicate, 2 parts by weight of sodium gluconate, 0.9 parts by weight of sodium octylate, 0.1 parts by weight of sodium 2-octenoate, 1 part by weight of γ-diethylenetriaminopropyltrimethoxysilane, 1.5 parts by weight of LAS and 0.1 parts by weight of defoamer, stir to dissolve, then add deionized water to a total weight of 50 parts by weight of all materials, stir evenly, and obtain a concentrated solution of the corrosion inhibitor composition.
[0128] 2. Preparation of solution for corrosion inhibitor composition evaluation
[0129] The concentrated solution of the corrosion inhibitor composition was diluted with deionized water to obtain a dilute solution of the corrosion inhibitor composition with a sodium metasilicate concentration of 0.1%, which was used as a solution for evaluating the corrosion inhibition performance of the corrosion inhibitor composition.
[0130] After evaluation, the appearance rating of the test piece was 0, and the corrosion inhibition rate was 96.0%.
[0131] [Example 8]
[0132] To 30 parts by weight of deionized water, add 1 part by weight of sodium metasilicate, 2 parts by weight of sodium gluconate, 0.9 parts by weight of sodium octanoate, 0.1 parts by weight of sodium isooctanoate, 1 part by weight of γ-diethylenetriaminopropyltrimethoxysilane, 1.5 parts by weight of LAS and 0.1 parts by weight of defoamer, stir to dissolve, then add deionized water to a total weight of 50 parts by weight of all materials, stir evenly, and obtain a concentrated solution of the corrosion inhibitor composition.
[0133] 2. Preparation of solution for corrosion inhibitor composition evaluation
[0134] The concentrated solution of the corrosion inhibitor composition was diluted with deionized water to obtain a dilute solution of the corrosion inhibitor composition with a sodium metasilicate concentration of 0.1%, which was used as a solution for evaluating the corrosion inhibition performance of the corrosion inhibitor composition.
[0135] After evaluation, the appearance rating of the test piece was 0, and the corrosion inhibition rate was 99.2%.
[0136] [Example 9]
[0137] 1. Preparation of Corrosion Inhibitor Concentrate
[0138] To 30 parts by weight of deionized water, add 1 part by weight of sodium metasilicate, 2 parts by weight of sodium gluconate, 0.85 parts by weight of sodium octanoate, 0.15 parts by weight of sodium isooctanoate, 1 part by weight of γ-diethylenetriaminopropyltrimethoxysilane, 1.5 parts by weight of LAS and 0.1 parts by weight of defoamer, stir to dissolve, then add deionized water to a total weight of 50 parts by weight of all materials, stir evenly, and obtain a concentrated solution of the corrosion inhibitor composition.
[0139] 2. Preparation of solution for corrosion inhibitor composition evaluation
[0140] The concentrated solution of the corrosion inhibitor composition was diluted with deionized water to obtain a dilute solution of the corrosion inhibitor composition with a sodium metasilicate concentration of 0.1%, which was used as a solution for evaluating the corrosion inhibition performance of the corrosion inhibitor composition.
[0141] After evaluation, the appearance rating of the test piece was 0, and the corrosion inhibition rate was 96.3%.
[0142]
Blank test
[0143] After the blank test, the appearance rating of the test piece was 3.
Claims
1. 7 Series aluminum corrosion inhibition composition, in parts by weight, comprises the following components: Alkali metal silicate, 1 part; Polyhydroxy acid alkali metal salt, 1-5 parts; Alkali metal salt of fatty acid, 0.1 to 1.5 parts.
2. The corrosion inhibition composition according to claim 1, characterized in that The composition of the alkali metal silicate conforms to the following formula 1: M2O﹒ nSiO2, formula 1; Wherein M represents an alkali metal, n represents the molar ratio of SiO2 to M2O, and preferably n is 0.5 to 3.
3. The corrosion inhibition composition according to claim 1, characterized in that The polyhydroxy acid-alkali metal salt conforms to the following formula 2: Wherein Q represents an alkali metal, and m=3-5.
4. The corrosion inhibition composition according to claim 1, characterized in that The fatty acid alkali metal salt conforms to RCOOT, wherein R is a C5-C8 straight-chain or branched fatty hydrocarbon group, and T represents an alkali metal.
5. The corrosion inhibition composition according to claim 1, characterized in that: The corrosion inhibition composition comprises 0.1 to 1.5 parts of a film-forming agent.
6. The corrosion inhibition composition according to claim 5, characterized in that: The film-forming agent conforms to the following formula 3: in: R1 and R2 are independently C1-C3 alkyl; X is an aliphatic group having 3 to 10 carbon atoms, the aliphatic group contains an amino group, and the amino group includes a primary amino group and a secondary amino group; preferably, the ratio of the number of atoms of the amino group N in X to the number of atoms of Si in Formula 3 is 2 or more, and X is connected to Si in Formula 3 through the carbon atom in X; Y is an aliphatic group having 3 to 10 carbon atoms, the aliphatic group contains an amino group, and the amino group includes a primary amino group and a secondary amino group; preferably, the ratio of the number of atoms of the amino group N in Y to the number of atoms of Si in Formula 3 is greater than 2, and Y is connected to Si in Formula 3 via a carbon atom in Y; or Y is a C1 to C3 alkoxy group (such as methoxy, ethoxy, n-propoxy or isopropoxy).
7. The corrosion inhibition composition according to claim 6, characterized in that: The corrosion inhibition composition comprises 0.1 to 5 parts of a surfactant; the surfactant is preferably an anionic surfactant or a nonionic surfactant; the anionic surfactant preferably comprises at least one selected from the group consisting of alkyl sulfates, alkylbenzene sulfonates and alcohol ether sulfates, and the anionic surfactant is preferably an alkali metal salt or a triethanolammonium salt; for example but not limited to, the alkyl sulfate is sodium dodecyl sulfate, referred to as K12; for example but not limited to, the alkylbenzene sulfonate can be sodium dodecylbenzene sulfonate, referred to as LAS; for example but not limited to, the alcohol ether sulfate is sodium fatty alcohol polyoxyethylene ether sulfate, the fatty alcohol is a C12 to C15 fatty alcohol, and the number of ethylene oxide units is 2 to 3; the nonionic surfactant is further preferably a nonionic surfactant with an HLB value of 8 to 18, and the most preferred nonionic surfactant is a HLB value of 13 to 18; the nonionic surfactant preferably comprises at least one selected from the group consisting of ethylene oxide propylene oxide copolyether, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and fatty amine polyoxyethylene ether.
8. The corrosion inhibition composition according to any one of claims 1 to 7, characterized in that: The corrosion inhibition composition includes 30 to 1000 parts of water.
9. Use of the corrosion inhibition composition according to claims 1 to 8 in the surface corrosion protection of 7 series aluminum materials.